Analysis of Chloride Levels in Well and PDAM Water in Ngelom Village, Sidoarjo - Khoirul Ngibad; Dheasy Herawati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Chloride is an anion that dissolves easily in water samples and it is the main inorganic anion founded in water samples. Excess of chloride ions in drinking water can damage the kidneys. The aims of this study is to determine chloride levels in well and PDAM water samples in Ngelom Village. Determination of chloride levels in water samples using the Mohr argentometric titration method. The samples used was well water and PDAM water, each was taken from 20 locations in Ngelom Village. The samples were mixed with K2CrO4 indicator and then were titrated using the silver nitrate standard solution until the end point of the titration was marked with a brick red color. The results of the analysis of chloride levels in well water of 92 to 491 mg/L and in PDAM of 57 to 230 mg/L. Based on these results, it can be concluded that chloride levels in both well water and PDAM water samples were below maximum threshold which appointed in Permenkes RI No. 416/Menkes/Per/IX/1990 (≤600 mg/L).